Microwave-assisted acetosolv extraction of lignin from empty fruit bunch fibers for fully bio-based formaldehyde-free phenolic thermosets applications - Muhammad Nor Arifin, Yaakob (2022)
Phenol-formaldehyde (PF) resole commonly used as an exterior thermosetting adhesive in a wide field of engineering applications. However, there are some issues regarding its raw materials being made from petroleum resources, which can be considered harmful chemicals. Therefore, there is an interest in substituting these raw materials with bio-based materials, which are more environmentally and user friendly. Although some studies have reported the utilization of bio-based materials in the production of bio-based PF, the complete substitution of both petro-based materials is still lacking. This research serves this purpose by investigating the essential aspects of substituting both petro-based materials in the production of PF resin. In this study, a resole-type phenolic resin was synthesized by utilizing the phenolic precursor (phenol and microwave-assisted acetosolv lignin extracted from empty fruit bunch (EFB)) and aldehyde precursor (formaldehyde, glyoxal, and terephtalaldehyde). The reaction was conducted under alkaline conditions at 100 °C for 4 hours. The lignin was chosen based on the highest yield produced during the microwave-assisted acetosolv method. In this study, the lignin was extracted by utilizing H2SO4 at 110 ℃ for 30 minutes, which produced the highest lignin yield (76.98%) aside from its high purity content (94.15%). From the lignin’s extraction result, it was observed that the yield of lignin obtained via utilization of Bronsted (H2SO4) is slightly greater compared to utilization of Lewis acid (AlCl3), and that Chromium (III) nitrate is not suited for lignin extraction. Based on Fourier Transform Infrared (FTIR), Proton Nuclear Magnetic Resonance (H NMR), and Thermogravimetric analysis (TGA), the extraction method with various acid catalysts revealed that the extracted lignins had similar structural and thermal characteristics. The produced resole resins were labeled as PF (phenol-formaldehyde), PG (phenol-glyoxal), PT (phenol-terephtalaldehyde), LF (lignin-formaldehyde), LG (lignin-glyoxal), and LT (lignin-terephtalaldehyde) resins. The Fourier Transform Infrared Spectroscopy (FTIR) showed that all the resole resins are composed of methylene bridges, which confirmed that the polymerization had taken place and the production of lignin-based or the fully bio-based phenolic resins was successful. Regarding thermal stability, the lignin-based resole resin showed low thermal stability compared to phenol-based resins due to the low number of sites for reactions to occur compared to phenol, which can be seen by the fast degradation of lignin-based resole, especially at temperatures below 100 °C. However, the curing peak shown by the DSC spectra proves that the value agrees with the result reported by a previous study (150–320 °C). Thus, from these findings, it can be concluded that lignin has a good potential for use as a phenolic precursor, and lignin-based phenolic resins can be a suitable candidate to substitute the commercially available phenolic resins.